Classroom Management Difficulties of Practice Teaching Program Faced by English College Students. - Khulaifiyah, Khulaifiyah (Program Studi Pendidikan Bahasa Inggris FKIP UIR, 2017)
Classroom managementis avariety oftypesof activitiesthat intentionallydonebythe teacherin order to createoptimalconditionsfortheteaching and learning processinthe classroom, consist of pre-learning activity, opening, learning activity and closing.This research was to find English students difficulties in managing classroom on practice teaching. The target population of this research was  the eight semester students English  Academic Year 2012/2013 of FKIP UIR. It was a descriptive research. The instrument were questionaires and interviews.The result of quesionnare and interview of the research show that students who already done practice teaching program still had difficulties in;Pre-Learning, such as checking the readiness of students, space, tools and media.Opening the lesson when practice teaching such as giving apperceptions and delivering competencies (objectives to be achieved) and action plans, and got difficult in doing Learning activityin a systematicstructure and stages. The last, got difficult to closing and giving reflection or create a summary by involving students and do a follow-up to give direction or activity or task as part of remedial or enrichment.